2015
DOI: 10.18203/2349-3259.ijct20150593
|View full text |Cite
|
Sign up to set email alerts
|

8-Hydroxydeoxyguanosine (8-OHdG) levels in urinary samples of pesticide sprayers on exposure to organophosphorus pesticides

Abstract: <p class="abstract"><strong><span lang="EN-US">Background: </span></strong><span lang="EN-US">Free radicals and other reactive species are constantly generated <em>in vivo</em> and cause oxidative damage to biomolecules. DNA is probably the most biologically significant target of oxidative attack. Among numerous types of oxidative DNA damage the formation of 8-hydroxyguanosine (8-OHdG) is a sensitive biomarker of oxidative stress, an adduct formed as a result of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…It was interesting to note that there is no significant difference between the 8-OHdG levels and their personal habits such as smoking and alcohol consumption, among all the three groups of study subjects. Similar observations were made earlier among pesticide sprayers (Mishra et al 2015). On contrary, another study conducted elsewhere reported elevated levels of 8-OHdG and strong association with smoking (Kulikowska-Karpińska and Czerw 2015; El-Khawanky et al 2018).…”
Section: Discussionsupporting
confidence: 79%
“…It was interesting to note that there is no significant difference between the 8-OHdG levels and their personal habits such as smoking and alcohol consumption, among all the three groups of study subjects. Similar observations were made earlier among pesticide sprayers (Mishra et al 2015). On contrary, another study conducted elsewhere reported elevated levels of 8-OHdG and strong association with smoking (Kulikowska-Karpińska and Czerw 2015; El-Khawanky et al 2018).…”
Section: Discussionsupporting
confidence: 79%
“…A correlation between the concentration of arsenic in the blood and the level of 8-OHdG in the urine was found [ 26 ]. Also, an influence of other xenobiotics on the increase of 8-OHdG concentration in blood or urine was described [ 28 , 42 ]. Some papers also describe the impact of smoking or exposure to carcinogens contained in tobacco smoke on the increase in 8-OHdG concentration [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is also evidence of the importance of genetic predisposition to BC, especially the slow acetylation genotype NAT2 [ 5 , 6 , 53 ]. Several studies also point to 8-OHdG and GST π as markers of exposure and the ability of detoxification of the body [ 21 , 22 , 26 28 ]. The significant contribution of exposure to carcinogens to the development of BC necessitates the search for markers that reflect individual sensitivity to environmental toxins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation